(untitled) (Palíndromo, 2026)
Text based on the experience embodied in the Laboratory and Performance “Insubordinados del Deseo” (Insubordinates of Desire) carried out collectively in Santiago, Chile, on the 25th anniversary of Pride in June 2025.